The effect of technological context on smart home adoption in Jordan - Adai Al-Momani; Mohd Nordin Abdul Rahman; Mohammed N. Al-Refai; Suhaila Abuowaida; Mohammad Arabiat; Nawaf Alshdaifat (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This research examines the use of internet of things (IoT) smart home technologies in Jordan, using the technologies-organization-environment (TOE) framework and social exchange theory (SET). This study investigates the influence of security and privacy considerations on the behavioral intention to embrace IoT smart home solutions. The research examines the function of trust (TR) in service providers as a mediator and investigates how information technology (IT) knowledge acts as a moderator between technological elements and behavioral intention. Analyzed using smart partial least squares (PLS), data from 315 responses of executives in both listed and non-listed businesses were examined. The results highlight the need of giving priority to technological factors and building TR in service providers to ensure the effective implementation of IoT smart home technology in Jordan.